Development of bilayer tissue-engineered scaffolds: combination of 3D printing and electrospinning methodologies - YILMAZ, HİLAL; GÜNDÜZ, OĞUZHAN (My University, 2024)
Although different fabrication methods and biomaterials are used in scaffold development, hydrogels and electrospun materials that provide the closest environment to the extracellular matrix have recently attracted considerable interest in tissue engineering applications. However, some of the limitations encountered in the application of these methods alone in scaffold fabrication have increased the tendency to use these methods together. In this study, a bilayer scaffold was developed using 3D-printed gelatin methacryloyl (GelMA) hydrogel containing ciprofloxacin (CIP) and electrospun polycaprolactone (PCL)-collagen (COL) patches. The bilayer scaffolds were characterized in terms of chemical, morphological, mechanical, swelling, and degradation properties; drug release, antibacterial properties, and cytocompatibility of the scaffolds were also studied. In conclusion, bilayer GelMA-CIP/PCL-COL scaffolds, which exhibit sufficient porosity, mechanical strength, and antibacterial properties and also support cell growth, are promising potential substitutes in tissue engineering applications.
Keywords: Biyomedikal Mühendisliği; Mühendislik ve Teknoloji; Biomedical Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; Malzeme Bilimi; MALZEME BİLİMİ, BİYOMATERYAL; MÜHENDİSLİK, BİYOMEDİKAL; Engineering, Computing & Technology (ENG); ENGINEERING; MATERIALS SCIENCE; MATERIALS SCIENCE, BIOMATERIALS; ENGINEERING, BIOMEDICAL; Biyomühendislik; Fizik Bilimleri; Biyomalzemeler; Biyomedikal mühendisliği; Bioengineering; Physical Sciences; Biomaterials; bilayer scaffold; ciprofloxacin; collagen; gelatin methacryloyl; polycaprolactone; tissue engineering